Contributions of student organization spolitically and in the media during the Liberation Revolution (1954/1962) - Azza, Al-Hussein (The Algerian Historical Journal, 2026)
The article deals with the study and analysis of the political role of student organizations politically and in the media during the liberation revolution (1954/1962). As well as the militant role played by the elements belonging to it until the date of its final dissolution. I explained in detail the political and media contributions of student organizations inside and outside Algeria. And how it contributed to the internationalization of the Algerian issue in international forums. Not to mention the jihadi and revolutionary role following the historical statement from the leadership of the revolution of the need for students to join its ranks due to its need for educated competencies.